2001
DOI: 10.1007/s005340100026
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Our preliminary clinical results suggest the tolerability and the considerable potential advantage of using cytoreductive resection with preoperative chemotherapy, intraoperative chemo-hyperthermia, and external beam postoperative radiotherapy for the management of advanced adenocarcinoma of the pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The median OS of the mEHT group was 18 months (range = 1.5-68 months) and was in agreement with 18.5 months of Kouloulias et al 56 and 18.6 months of Ohguri et al 33 The OS analysis of 201 patients in the 14 published studies on hyperthermia for pancreatic cancer treatment showed an overall median survival 10.5 months (range = 1-53 months), 21 which was lower than the median OS (18 months) of mEHT group as reported in the present study. The survival curves after a certain period converge because the therapies both with and without mEHT have selected the patients with more favorable characteristics.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The median OS of the mEHT group was 18 months (range = 1.5-68 months) and was in agreement with 18.5 months of Kouloulias et al 56 and 18.6 months of Ohguri et al 33 The OS analysis of 201 patients in the 14 published studies on hyperthermia for pancreatic cancer treatment showed an overall median survival 10.5 months (range = 1-53 months), 21 which was lower than the median OS (18 months) of mEHT group as reported in the present study. The survival curves after a certain period converge because the therapies both with and without mEHT have selected the patients with more favorable characteristics.…”
Section: Discussionsupporting
confidence: 90%
“…This low mEHT toxicity correlation has been shown also in previous studies. 21,32-35,54-56 This may suggest a better safety of the mEHT than the conventional hyperthermia that resulted in 935 complains from 70 hyperthermia treatments as reported in a recent study. 56…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations